OPTIMIZATION OF FREEZE VALVE DESIGN FOR PASSIVE SAFETY SYSTEMS IN MOLTEN SALT REACTOR - Dany Riupassa, Robi
Molten Salt Reactor (MSR) is one of the generation IV nuclear reactors designed with a passive safety system. Passive safety systems are needed to deal with emergency conditions at nuclear reactors. Nuclear reactor accidents can occur due to pump failure or power loss. MSR uses a freeze valve to overcome the reactor core temperature rise due to the decay heat after shutdown. If it is not handled properly, in a short time it can make the reactor core melt. The freeze valve functions as a blockage which will automatically open when the reactor core temperature rises. When the blockage opens, the fuel from the reactor core will flow to the emergency dump tank. It is very important to calculate the fuel drain time before the reactor core is damaged. In this study, a modification of the freeze valve design was developed from other researchers with a new type that would give more heat transfer modes. This new type consists of two parts, namely the head plug and neck plug and added heating rings. The design specifications of this system will be tested for fuel in the form of FLiNaK (LiF-NaF-KF: 46.4-11.5-42 mole%). Heating rings, reactor vessels, and drainage pipes use Hastelloy-N material. Freeze valve uses Cesium Chloride (CsCl). This study includes computer and optimization of simulation results. Computer simulation is done using CFD and deep learning model. The heat transfer process simulation uses a heat transfer in solids module while the melting behavior simulation uses a heat transfer with phase change module.